Heart rate recovery responses after acute training load changes in top-class water polo players - Botonis, P. G.; Arsoniadis, G. G.; Platanou, T. I.; Toubekis, A. G. (European Journal of Sport Science, 2021)
The purpose of the study was to investigate the effects of acute training load changes of elite water polo players on heart rate recovery (HRR) responses after a standardized swimming test. Nine water polo players were tested after a two-day light-load and two-day heavy-load training. Preliminarily, critical swimming speed was calculated. Testing comprised of an intermittent 4 × 100-m swimming separated by 10 s of rest with an intensity corresponding to 85% of their maximum speed previously attained during a 100-m swim test followed immediately by assessment of HRR. Internal training load (ITL) was measured using the rating of perceived exertion and the duration of training sessions. The swimming speed corresponded to 1.43 ± 0.06 m·s-1 and 1.45 ± 0.06 m·s-1 after light-load and heavy-load training, respectively (p=0.06, d=0.74). ITL was increased in high-load compared to light-load training (p<0.001, d=11.54). The difference in HR at end of exercise (HR-end) and after 60 s rest and the difference in mean HR during last min of exercise and HR after 60 s rest were higher in light-load training (p<0.05, d=0.85-1.15). The absolute change in ITL was correlated with the respective change in the percentage change of HR-end at 10 seconds of recovery (%HRR10s) (r=0.72, p=0.03). Significant correlation was observed between the percentage change of ITL with the %HRR10s (r=0.67, p=0.05). We conclude that HRR tracks acute changes in training load. The lower HRR following high-load training likely indicates a blunted parasympathetic re-activation.